1997
DOI: 10.1073/pnas.94.21.11333
|View full text |Cite
|
Sign up to set email alerts
|

MRIT, a novel death-effector domain-containing protein, interacts with caspases and BclX L and initiates cell death

Abstract: Activation of the cascade of proteolytic caspases has been identified as the final common pathway of apoptosis in diverse biological systems. We have isolated a gene, termed MRIT, that possesses overall sequence homology to FLICE (MACH), a large prodomain caspase that links the aggregated complex of the death domain receptors of the tumor necrosis factor receptor family to downstream caspases. However, unlike FLICE, the C-terminal domain of MRIT lacks the caspase catalytic consensus sequence QAC(R͞Q)G. Nonethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
172
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 223 publications
(177 citation statements)
references
References 23 publications
4
172
1
Order By: Relevance
“…Both MC159L and E8 lack such an ability (Bertin et al, 1997;Hu et al, 1997a;Thome et al, 1997 and our unpublished results). However, like ORF-K13, the DEDs-containing prodomains of Caspase 8 and MRIT/cFLIP have been reported to induce apoptosis when over-expressed in mammalian cells Han et al, 1997;Shu et al, 1997). We have recently discovered that the prodomains of Caspase 8 and MRIT/cFLIP, like ORF-K13, can also activate the NF-kB pathway (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both MC159L and E8 lack such an ability (Bertin et al, 1997;Hu et al, 1997a;Thome et al, 1997 and our unpublished results). However, like ORF-K13, the DEDs-containing prodomains of Caspase 8 and MRIT/cFLIP have been reported to induce apoptosis when over-expressed in mammalian cells Han et al, 1997;Shu et al, 1997). We have recently discovered that the prodomains of Caspase 8 and MRIT/cFLIP, like ORF-K13, can also activate the NF-kB pathway (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…The expression constructs for the death receptors, RIP, Caspase 8, CrmA, MRIT, E8 and MC159L have been described previously Han et al, 1997;Hu et al, 1997a). Constructs encoding ORF-K13 (GenBank U90534) were prepared by PCR ampli®cation of the desired coding sequence from a human genomic DNA sample containing KSHV/HHV8 (human herpesvirus 8) genomic DNA which was obtained from Dr Tim Rose (University of Washington, Seattle, WA, USA).…”
Section: Expression Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no obvious molecular mechanism linking anti-apoptotic Bcl-2 family members with the classical type 1 CD95/ FADD/caspase-8 pathway. Although it has been suggested that Bcl-2 and Bcl-X L directly (Boise and Thompson, 1997) or indirectly (Chinnaiyan et al, 1997;Han et al, 1997;Ng et al, 1997;Hu et al, 1998) bind caspase-8 and so modulate its activation (Medema et al, 1998), a recent report indicates that, in a system in which Bcl-X L e ectively suppresses CD95-induced apoptosis, Bcl-X L neither interacts with caspase-8 nor inhibits its recruitment or activation (Medema et al, 1998). This ®nding seems to leave little room for a role for Bad as an intermediary modulating activation of caspase-8 by FADD.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Cellular FLICE-inhibitory protein (c-FLIP) specifically regulates the DR apoptotic process. [3][4][5][6][7][8][9] c-FLIP is expressed in both a long-form (c-FLIP L ) and a short-form (c-FLIP S ) due to alternative splicing. The DEDs of c-FLIP L and c-FLIP S interact with the DEDs of FADD and procaspasse-8.…”
Section: Introductionmentioning
confidence: 99%